Predictors of Electronic Learning Self-Efficacy: A Cross-Sectional Study in Saudi Arabian Universities - Aldhahi, Monira I.; Baattaiah, Baian A.; Alqahtani, Abdulfattah S. (Frontiers in Education, 2021)
This study aims at describing academic self-efficacy in online learning and exploring the determinant factors of learners’ academic self-efficacy. In this cross-sectional survey-based study, 892 respondents voluntarily participated in and completed the survey. Online learning self-efficacy was assessed using an online academic self-efficacy questionnaire. The sociodemographic characteristics showed that 85% of the respondents were female, 21% were medical students, and 13% were postgraduate students. Most respondents reported insufficient self-efficacy for learning and time management, whereas 51% showed good self-efficacy for technology. When considering the study’s field, more medical students reported good self-efficacy scores for learning and technology (36% and 68%, respectively) than non-medical students (33% and 47%, respectively). Time management self-efficacy was mostly reported to be good (47%) among those with a high GPA. The results showed that educational status, the field of study, and learning satisfaction were significant predictors of self-efficacy for learning and technology (p < .001). Gender, academic performance, and learning satisfaction were significant predictors of self-efficacy for time management (p < .001). Self-efficacy can play a major role in online learning, particularly in circumstances like the sudden transformation of the educational system that has occurred during the COVID-19 pandemic. An effective academic self-efficacy of learning, use of technology, and time management skills should also be emphasized. The value of this research lies in exploring electronic learning self-efficacy and its predictor among university students. The research findings help us improve students’ academic self-efficacy to enhance the learning environment by planning new studies.